Matharpacady-26.jpg - Mumbai Archive Project Team (Jio Institute, 2024)
The Holy Cross Oratory is the most notable religious landmark in Matharpacady. This small chapel was built on land donated by Mrs Buthello and constructed in response to a devastating plague that struck the city in 1875 (another plague struck in 1896). The residents came together to collectively build the chapel, praying for the plague to spare the village. Miraculously, not a single death occurred at Matharpacady in the plague and the community has maintained the tradition of holding yearly feasts, now in its 148th year.